Profile of scientific researchers from the northeast and southeast regions of Brazil (Research, Society and Development, 2022)
In recent decades, it has been observed that in the areas of medicine, physics, humanities, social sciences and engineering there has been a notable increase in scientific production. Research is important to foster scientific production, especially in the Northeast, a region where well-known professionals have little access to graduate programs. The aim of this study was to write the profile of Postgraduate Researchers from Public Institutions in the Northeast and Southeast regions. It is a field research of basic nature, of the documentary retrospective type with a quantitative approach to the data. Data collection lasted 4 months and was carried out directly by the researchers, through access to the CNPq Lattes platform in the Data and Statistics section. It was observed that scientific production is strongly concentrated in the southeast region of Brazil, both in master's and doctoral programs. Doctoral programs also increase the form of growth in Brazil, but it is still smaller than master's programs. The data presented show that Brazil faces several challenges with regard to the development and consolidation of its National Innovation System. Among them, they stand out as a need to encourage Research and Development activities. The research results clearly demonstrate the existence of inequalities in the quantity of scientific production in the regions. They stand out as a need to encourage Research and Development activities in the regions to reverse these inequalities.